Anomalously Strong Second‐Harmonic Generation in GaAs Nanowires via Crystal‐Structure Engineering. (24th June 2021) - Zhang, Bin; Stehr, Jan E.; Chen, Ping‐Ping; Wang, Xingjun; Ishikawa, Fumitaro; Chen, Weimin M.; Buyanova, Irina A.
Abstract: GaAs‐based semiconductors are highly attractive for diverse nonlinear photonic applications, owing to their non‐centrosymmetric crystal structure and huge nonlinear optical coefficients. Nanostructured semiconductors, for example, nanowires (NWs), offer rich possibilities to tailor nonlinear optical properties and further enhance photonic device performance. In this study, it is demonstrated highly efficient second‐harmonic generation in subwavelength wurtzite (WZ) GaAs NWs, reaching 2.5 × 10 −5 W −1, which is about seven times higher than their zincblende counterpart. This enhancement is shown to be predominantly caused by an axial built‐in electric field induced by spontaneous polarization in the WZ lattice via electric field‐induced second‐order nonlinear susceptibility and can be controlled optically and potentially electrically. The findings, therefore, provide an effective strategy for enhancing and manipulating the nonlinear optical response in subwavelength NWs by utilizing lattice engineering. Abstract : Highly efficient second‐harmonic generation is demonstrated in subwavelength wurtzite GaAs nanowires (NWs) that are about seven times higher than those in their zincblende counterparts. This high efficiency is attributed to an axial built‐in electric field in the wurtzite lattice. These findings provide an effective strategy for enhancing and manipulating the nonlinear optical response in subwavelength NWs by utilizing lattice engineering.